2019
DOI: 10.1371/journal.pone.0217273
|View full text |Cite
|
Sign up to set email alerts
|

The prediction of early preeclampsia: Results from a longitudinal proteomics study

Abstract: Objectives To identify maternal plasma protein markers for early preeclampsia (delivery <34 weeks of gestation) and to determine whether the prediction performance is affected by disease severity and presence of placental lesions consistent with maternal vascular malperfusion (MVM) among cases. Study design This longitudinal case-control study included 90 patients with a normal pregnancy and 33 patients with early preeclampsia. Two to six maternal plasma samples were co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
65
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(71 citation statements)
references
References 251 publications
(165 reference statements)
4
65
0
2
Order By: Relevance
“…The diagnostic performance of the panel was similar among the different types of PE (earlyonset vs. late-onset, mild vs. severe). Compared to a recent proteomics study where different models were predictive at different GA windows [64], our model with 6 proteins works across 5-30 wks of GA, which is more useful when exact gestational age is unknown. Therefore, this model may offer a new investigational approach towards the understanding of placental biology during pregnancy as well as guiding innovative methods for PE diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…The diagnostic performance of the panel was similar among the different types of PE (earlyonset vs. late-onset, mild vs. severe). Compared to a recent proteomics study where different models were predictive at different GA windows [64], our model with 6 proteins works across 5-30 wks of GA, which is more useful when exact gestational age is unknown. Therefore, this model may offer a new investigational approach towards the understanding of placental biology during pregnancy as well as guiding innovative methods for PE diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…Recent years have seen important progress in understanding the pathogenesis of this disorder, as well as its prevention [2]. Additionally, a wide range of potential biomarkers for prediction of preeclampsia have been studied: maternal characteristics (African-American ethnicity, body mass index, pregestational diabetes mellitus, systolic blood pressure, educational level), pregnancy-associated plasma protein A (PAPP-A), A Disintegrin and Metalloprotease 12 (ADAM-12), placental growth factor (PlGF), soluble fms-like tyrosine kinase 1 (sFlt-1), placental protein 13 (PP13), proteomics studies, Doppler ultrasonography, and many others [3][4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Early PE (onset <34th week) is characterized by a more severe course, more frequent complications in the mother, and complications in the fetus (intrauterine growth restriction (IUGR), as well as fetal hypoxia or death of the fetus), which may suggest a significant contribution of placental circulation pathology. In late PE, the placenta is often normal; therefore, this form of the disease may be characterized by a lower frequency of fetal complications [13,16,[27][28][29]. It was also found that PE manifesting mainly maternal symptoms may display risk factors similar to those of GH (obesity, insulin-resistance, hyperlipidemia, and chronic hypertension), which may suggest the presence of disorders in the mother's blood vessels before pregnancy [13].…”
Section: Discussionmentioning
confidence: 99%